Acute oral toxicity and anti-inflammatory evaluation of methanolic extract of Rotula aquatica roots in Wistar rats - Vysakh, A. (J Ayurveda Integr Med, 2020)
BACKGROUND: The plant Rotula aquatica Lour. was traditionally well known due to its large number of pharmacological action and medicinal uses. The plant is a necessary component of many Ayurvedic drug preparations since historical times. It is widely used as a crucial ancient drug for kidney and bladder stones. OBJECTIVES: The main objective of the study was to evaluate the acute toxicity and anti inflammatory efficacy of methanolic extract of R.aquatica Lour. in in vivo models. MATERIALS AND METHODS: The qualitative phytochemical analysis and invitro antioxidant activity of the roots of methanolic extract of R.aquatica Lour. (MERA) was evaluated. The acute toxicity effect of MERA was evaluated with two different doses (550, 2000 mg/kg body weight), were administrated orally to Wistar rats. The rats were observed for sign and symptoms of toxicity and mortality for 14 days. The parameters measured including relative organ weight, blood, biochemical and histopathological parameters of hepatic and renal toxicity. The anti-inflammatory effect of MERA was also evaluated in carrageenan and dextran-induced paw edema models. RESULTS: The phytochemical evaluation of MERA shows the presence of secondary metabolites like alkaloids, flavonoids, phenolics and tannins, phytosterols, reducing sugars, proteins and terpenoids. The results of in-vitro antioxidant evaluation of MERA reveal its capability to scavenging free radical at a lower concentration. The MERA did not show any visible signs of toxicity up to the dose of 2000 mg/kg body weight. The results obtained from our carrageenan and dextran-induced paw edema model study also proved the anti-inflammatory effect of MERA in rat model. CONCLUSION: The result shows the potential of MERA as an anti-inflammatory drug to reduce the signs of inflammation devoid of any toxic effect.